On Employee Vice - Moberg, Dennis J. (Business ethics quarterly, 1997)
Vice is a neglected concept in business ethics. This paper attempts to bring vice back into the contemporary dialogue by exploring one vice that is destructive to employee and organization alike. Interestingly, this vice was first described by Aristotle as akolastos. Drawing extensively on the criminology literature, the findings challenge both common sense and popular images of white-collar crime and criminals. While not all instances of employee betrayal are attributable to vice, some most certainly are, and the paper offers a description of those violations of trust in which vice may play a role.